2017
DOI: 10.1016/j.jmps.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Guided waves in pre-stressed hyperelastic plates and tubes: Application to the ultrasound elastography of thin-walled soft materials

Abstract: In vivo measurement of the mechanical properties of thin-walled soft tissues (e.g., mitral valve, artery and bladder) and in situ mechanical characterization of thinwalled artificial soft biomaterials in service are of great challenge and difficult to address via commonly used testing methods. Here we investigate the properties of guided waves generated by focused acoustic radiation force in immersed pre-stressed plates and tubes, and show that they can address this challenge. To this end, we carry out both (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 50 publications
(61 reference statements)
1
27
0
Order By: Relevance
“…Its resulting phase speed plots are visualized in Fig. 5 and correspond well with the theoretical dispersion curves of the A-and S-modes for an inviscid plate submerged in water as described by Li et al [32]. For the transversal body force [ Fig.…”
Section: Statisticssupporting
confidence: 74%
See 3 more Smart Citations
“…Its resulting phase speed plots are visualized in Fig. 5 and correspond well with the theoretical dispersion curves of the A-and S-modes for an inviscid plate submerged in water as described by Li et al [32]. For the transversal body force [ Fig.…”
Section: Statisticssupporting
confidence: 74%
“…We will not consider SH modes, as the particle motion of these modes is along the plate surface perpendicular to the propagation direction [31] and is, therefore, probably hard to detect in cardiac parasternal and apical views. The A-and S-mode guided waves are characterized by different dispersion curves, as described in [31], [32], and [36]. S-modes are regularly referred to as longitudinal, and A-modes as transversal SWs because of the dominant particle motion with respect to the propagation direction in the centerline of the medium.…”
Section: A Guided Waves In the Heart Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al . 21 have recently shown that changes in nonlinearity parameter A can be detected via analysis of transient guided waves in pre-stressed medium. Using a simplistic cumulative stress-strain model, an earlier ex vivo study showed that nonlinear parameter changes drastically in aberrant tissue compared to the intact ones 22 .…”
Section: Introductionmentioning
confidence: 99%